التعدد اللغوي بين التفعيل المعرفي والأمن الهوياتي للدول - عباد,ريمة (University of Eloued جامعة الوادي, 2024)
ملخص: يعد التعدد اللغوي في المجتمعات المعاصرة من الرهانات الثقافية - السياسية ذات الصلة الوثيقة بقضايا الهوية والبناء المواطناتي والوحدة الوطنية. يهدف المقال إلى تحليل إشكالية تحقيق التوازن بين التفعيل المعرفي اللغوي والأمن الثقافي للدول في ظل تداعيات العولمة التي تطرح عديد التحديات المرتبطة أساسا باستقرار الدولة الوطنية وتفاعلاتها الدولية وفق مقتضيات الأمن الهوياتي، ولعل أهمية البحث تتجلى في التركيز على ما يمكن تسميته باللغويات السياسية كمجال اهتمام علمي حيوي جديد من شأنه تقديم نماذج تحليلية تُزاوج بين علم اللسانيات والعلوم السياسية في تحليل التفاعل الأمني الهوياتي. Abstract: Multilingualism in contemporary societies represents a cultural and political challenge closely linked to issues of identity, civic construction, and national unity. This article aims to analyse the dilemma of achieving a balance between linguistic cognitive activation and cultural security for nations in the face of the repercussions of globalization, these Repercussions pose numerous challenges primarily related to the stability of the nation-state and its international interactions, according to the requirements of identity security. The importance of this research seems evident in focusing on what is known as the political linguistics as a new vital scientific interest that would provide analytical models combining linguistics with political science while analysing the security-identity interaction of the international system units.
Keywords: تعدد لغوي; تفعيل لغوي; أمن ثقافي; تفاعلات دولية; multilingualism; Cognitive Activation; Cultural Security; international interactions